5‐Aminoimidazole‐4‐carboxamide ribonucleoside‐mediated adenosine monophosphate‐activated protein kinase activation induces protective innate responses in bacterial endophthalmitis. (26th July 2016) - Kumar, Ajay; Giri, Shailendra; Kumar, Ashok
Summary: The retina is considered to be the most metabolically active tissue in the body. However, the link between energy metabolism and retinal inflammation, as incited by microbial infection such as endophthalmitis, remains unexplored. In this study, using a mouse model of Staphylococcus aureus ( SA ) endophthalmitis, we demonstrate that the activity (phosphorylation) of 5' adenosine monophosphate‐activated protein kinase alpha (AMPKα), a cellular energy sensor and its endogenous substrate; acetyl‐CoA carboxylase is down‐regulated in the SA ‐infected retina. Intravitreal administration of an AMPK activator, 5‐aminoimidazole‐4‐carboxamide ribonucleoside (AICAR), restored AMPKα and acetyl‐CoA carboxylase phosphorylation. AICAR treatment reduced both the bacterial burden and intraocular inflammation in SA ‐infected eyes by inhibiting NF‐kB and MAP kinases (p38 and JNK) signalling. The anti‐inflammatory effects of AICAR were diminished in eyes pretreated with AMPK inhibitor, Compound C. The bioenergetics (Seahorse) analysis of SA ‐infected microglia and bone marrow‐derived macrophages revealed an increase in glycolysis, which was reinstated by AICAR treatment. AICAR also reduced the expression of SA ‐induced glycolytic genes, including hexokinase 2 and glucose transporter 1 in microglia, bone marrow‐derived macrophages and the mouse retina. Interestingly, AICAR treatment enhanced the bacterial phagocytic and intracellular killing activities of cultured microglia, macrophages and neutrophils. Furthermore, AMPKα1 global knockout mice exhibited increased susceptibility towards SA endophthalmitis, as evidenced by increased inflammatory mediators and bacterial burden and reduced retinal function. Together, these findings provide the first evidence that AMPK activation promotes retinal innate defence in endophthalmitis by modulating energy metabolism and that it can be targeted therapeutically to treat ocular infections.